2011
DOI: 10.1097/mao.0b013e31822558c4
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation After Complete Cochlear Coverage in Cochlear Implantation With the Free-Fitting FLEXSOFT Electrode Carrier

Abstract: This study showed that preservation of residual hearing is possible in a high number of subjects when a flexible electrode and atraumatic surgical techniques are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 34 publications
(20 reference statements)
4
33
0
4
Order By: Relevance
“…Near-complete HP is possible in a minority of patients when the full-length FLEXsoft electrode is inserted with minimal trauma, corroborating the results of Helbig et al (13) whose 21 patients, followed for a shorter period, achieved similar HP rates. Improved speech understanding was not seen in individuals with near-complete HP relative to others.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Near-complete HP is possible in a minority of patients when the full-length FLEXsoft electrode is inserted with minimal trauma, corroborating the results of Helbig et al (13) whose 21 patients, followed for a shorter period, achieved similar HP rates. Improved speech understanding was not seen in individuals with near-complete HP relative to others.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that most hearing loss happened at the time of surgery or shortly afterward, emphasizing the importance of meticulous surgical technique and atraumatic electrode design. In contrast, other studies have shown a measurable decrease in HP rates over time (3,13). Fibrosis, foreign body reaction and/or natural progression of disease may cause hearing loss that happens later.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…There is now converging data and an increasing number of reports on the possibility of deep electrode insertion and hearing preservation [Punte et al, 2010;Helbig et al, 2011;Usami et al, 2011]. This advantage may be used by the patient for better frequency resolution.…”
Section: Discussionmentioning
confidence: 99%